Estudo do perfil genético de linhagens de camundongos mantidos nos biotérios de criação de duas instituições parceiras na Rede Mineira de Bioterismo - Gabriel Barbosa de Oliveira (2013)
Genetic control is essential in managing colonies of inbred strains as genetic contamination of these lineages began to compromise the experimental results in laboratory animal science, becoming a serious problem among the scientific community. Contamination between strains of the same color and genetic differences due to genetic drift can bring an economic loss of large proportions, such as loss of resources invested in research, and wasted time and incorrect data in experiments. These genetic differences can greatly influence testing pharmacological and behavioral responses, and may remain unnoticed for a long period without the researcher to note that data from his work are compromised due to changing the genetic background of the animal used. Therefore, the genetic monitoring is an important factor to be considered and should be part of routine production of a animal facility. This study investigated the genetic profile of inbred mice kept in two Animal Facilities of Rede Mineira de Bioterismo, comprised of eight institutions in the State of Minas Gerais. Samples of inbred mouse strains BALB/c and C57BL/6 were collected from foundation colonies of animal facility production of Universidade Federal de Minas Gerais (UFMG) and the Center for Biology of Reproduction (CBR) at the Federal University of Juiz de Fora (UFJF). Samples were genotyped using polymorphic microsatellite markers 60 for both strains (BALB/c and C57BL/6). We selected three markers on chromosome making the 19 autosomal and X chromosome. The PCR products were analyzed after electrophoresis on agarose gel and compared to reference values available in the database MGI. Heterozygosity was observed in both strains maintained in the UFMG Animal Facility. About one fifth of the markers tested for BALB / c and 6.7% for the C57BL / 6 strain. In Animal Facility production UFJF were not observed heterozygosity for the inbred strains BALB / c and C57BL / 6. These results suggest the occurrence of genetic drift with the formation of sublineages on UFMG Animal Facility, due to the long stay period without renewal of the same. This information will provide the basis for development of genetic control routines in the new Animal Facility UFMG, which will start its activities with new colonies of animals in May this year, besides serving for exchange of information between Rede Mineira de Bioterismo.